Effect of pH on the hydrolytic kinetics of gamma-glutamyl transferase from bacillus subtilis - Balakrishna, Sharath; Prabhune, Asmita (Scientific World Journal, 2014)
The effect of pH on the steady state kinetics of gamma-glutamyl transferase (GGT) from Bacillus subtilis was examined using glutamyl-(3-carboxyl)-4-nitroanilide as the chromogenic reporter substrate. The enzyme was active in the pH range 7.0-11.0 with the optimum activity at pH 11.0. We noticed a pH dependent transformation in the nature of substrate consumption kinetics. The substrate saturation curves were hyperbolic in the pH range 7.0-9.0 but changed into sigmoid form at pH 10.0 and 11.0. Hill's coefficients were > 1. We also analysed the effect of pH on the structure of the enzyme. The circular dichroism spectra of the enzyme sample at pH 9.0 and 11.0 were coincidental in both far and near UV regions indicating conservation of the secondary and tertiary structures, respectively. Themolecular weight of the enzyme sample was the same in both pH 7.0 and 11.0 indicating conservation of the quaternary structure. These results show that the kinetic transformation does not involve significant conformational changes. Cooperative binding of multiple substrate molecules may not be the basis for the sigmoid kinetics as only one substrate binding site has been noticed in the reported crystal structures of B. subtilis GGT.